THE EFFECT OF WORK ETHIC AND JOB RESPONSIBILITY ON ACHIEVEMENT MOTIVATION WITH THE MODERATING VARIABLE OF THE WORK ENVIRONMENT AT PT YANMAR JAYA ELECTRIC - Amin Hou; Ester Hervina Sihombing; Prianda Pebri; Ratih Amelia; Ahmad Fadli (Jurnal Ekonomi, 2022)
Achievement motivation of employees at PT Yanmar Jaya Electrik can appear when their work ethic and if they have good responsibilities towards their work. However, the high and low achievement motivation can also be influenced by a good work environment. The results of this study used a sample of 100 permanent employees who had worked for 5 years and the results showed (1) the significant level of work ethic variable of 0.025 was smaller at = 0.05. So from the test results it is stated that partially the work ethic variable (X1) has a significant effect on employee achievement motivation (Y) at PT Yanmar Jaya Electric, (2) Position Responsibilities Variable with a significant level of 0.029 is smaller at = 0.05 then Partially, the Job Responsibility variable (X2) has a significant effect on employee achievement motivation (Y) at PT Yanmar Jaya Electric (3) Moderate 1 Variable (X1*Z) with a significant level of 0.016 is smaller at = 0.05. It means that the moderating variable of the work environment can moderate the relationship between work ethic and achievement motivation. (4) Moderate variable 2 (X2*Z) has a significant level of 0.423 which is greater at = 0.05. So it means that the moderating variable of the work environment is not able to moderate job responsibilities on achievement motivation